Syntactic Networks of Interlanguage Across L2 Modalities and Proficiency Levels - Hao, Yuxin; Wang, Xuelin; Wu, Meng; Liu, Haitao (Frontiers in Psychology, 2021)
Over time, interlanguage studies has shifted from the early qualitative studies to the quantitative studies of specific linguistic structures. However, the focus of these studies is usually on one aspect of an interlanguage, instead of the whole system. The ideal object of interlanguage research is a second language (L2) learner’s language system, for only in this way can the entire L2 learning process be examined. As a self-organizing and self-regulated system, the panorama of interlanguage can be revealed objectively through the complex network approach. In this study, we construct eight interlanguage dependency syntactic networks of varying proficiency levels and modalities, and conduct a quantitative study of the respective network parameters. We find that all syntactic networks of L2 learners initially present scale-free and small-world properties. This suggests varying regularities in the development of a syntactic network between interlanguage and native language acquisition. Moreover, the first language plays an important role in L2 development. Network parameters differentiate interlanguage modalities and five quantitative parameters can indicate L2 proficiency.